Russian Energy Security Strategy in Middle East: the international and political journal - Farhan, Assist.Prof Dr Shaima Maarouf (The International and Political Journal, 2025)
Energy security has a significant political priority and major component of national security for any country in the world. Accordingly, protecting energy security has no less importance than protecting the vital interests and goals of any country. This has prompted major countries - such as the United States, China, Russia, and Japan to develop clear strategies to achieve energy security in strategic regions, including the Middle East, which is one of the most important productions regions in the world.